Restrictions For OCL Constraint Optimization Algorithms - Mezei, Gergely; Levendovszky, Tihamér; Charaf, Hassan (Electronic Communications of the EASST, 2007)
Efficient constraint handling is essential in UML, in metamodeling as well as in model transformation. OCL is a popular, textual formal language that is used in most of the modeling frameworks to express constraints. Our research focuses on the optimization of OCL handling. Previous work have presented algorithms that can accelerate the constraint validation by rewriting and decomposing the constraints and caching the model queries. Although these algorithms can be used in general, there are special cases, where additional restrictions apply. The aim of this paper is to present these refined restrictions and the extended optimization algorithms.